Subthreshold region analysis for UTBOX and UTBB SOI nMOSFETs with different channel lengths and silicon thickness - Silva, V. C.P.; Sonnenberg, V.; Martino, J. A.; Simoen, E.; Claeys, C.; Agopian, P. G.D. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2017)
This paper presents an experimental analysis of the influence of the silicon thickness (tsi)and the channel length (L) on the threshold voltage (Vt), subthreshold swing (SS), drain induced barrier lowering (DIBL), gate induced drain leakage (GIDL) and the ON-state over OFF-state current ratio (ION/IOFF))on Ultra Thin Buried Oxide (UTBOX) and Ultra Thin Body and Buried oxide (UTBB) SOI nMOSFET devices. In order to complement this analysis, a simulation of the UTBB devices was performed. Devices with thinner silicon film present better control of short channel effects resulting in improved parameters such as SS(tsi=50nm → ∼ 85-90 mV/dec; tsi=20nm → ∼ 70-80 mV/dec), DIBL(tsi=50nm → ∼ 130-150 mV/V; tsi=20nm → ∼ 25-40 mV/V), GIDL and a reduction of the channel length influence on them. When comparing the UTBB devices without and with ground plane implantation (GP) it was noted that the GP did not affect the DIBL and GIDL parameters, but it increases Vt (∼0.25V without GP and ∼0.45V with GP), degrades SS and improves Ion/Ioff (from ∼ 105 without GP to ∼108 with GP).